USING MISTAKE BUSTER TECHNIQUE TO IMPROVE ENGLISH GRAMMATICAL MASTERY OF THE STUDENTS OF MA MA'ARIF AN-NUR WINONGAN - MOHAMAD FUAD BARAKWAN (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Grammatical aspect became an important aspect in learning process that have to be known by students. Based on this reality, the writer proposes to use “The Mistake Buster” technique to solve the problem. The researcher used Classroom Action Research (CAR) for this study. There are 27 students as the participant of this study, this study used 2 pieces of instruments, namely observations and grammar tests. The findings of this study showed that based on student data, it had known that there had been an increase of 92,5%. The value obtained by students had exceeded the minimum passion score (KKM) that had been determined. It had concluded that learning with the Mistake Buster Technique can improve the learning outcomes of the Recount Text theme in class X MA Ma'arif An-Nur Winongan.  Mistake Buster Technique had suggested to use was strategy for teacher as an appropriate strategy in teaching student’s grammar and for further researchers, the Mistake Buster Technique could be used for experimental research to improve English in improving language mastery, especially in the simple past tense.Keywords: Mistake Buster, Grammatical Mastery, Learning Technique